2021
DOI: 10.3389/fimmu.2020.607314
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of the Regulatory Mechanisms of Ace2 in the Infected Mouse Lung

Abstract: Acute lung injury (ALI) is an important cause of morbidity and mortality after viral infections, including influenza A virus H1N1, SARS-CoV, MERS-CoV, and SARS-CoV-2. The angiotensin I converting enzyme 2 (ACE2) is a key host membrane-bound protein that modulates ALI induced by viral infection, pulmonary acid aspiration, and sepsis. However, the contributions of ACE2 sequence variants to individual differences in disease risk and severity after viral infection are not understood. In this study, we quantified H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 94 publications
(121 reference statements)
0
13
0
Order By: Relevance
“…To determine whether the BXD family is suitable as a diversity model to define causal molecular networks modulating SARS pathogenesis and disease severity, we investigated whether the two founders, B6 and D2, differ significantly in susceptibility to MA15 infection. We first examined our existing transcriptomic data on the B6 and D2 parents and found that basal pulmonary levels of viral entry receptor Ace2 transcript are well matched [ 8 ], ruling out the possibility of pre-infection Ace2 expression as a confounding factor. We then challenged groups of 10-week old B6 ( n = 26) and D2 ( n = 28) via the intranasal route with 10 5 TCID 50 of MA15 virus (diluted in 50-μl phosphate-buffered saline, PBS), and monitored weight changes for 9 days.…”
mentioning
confidence: 99%
“…To determine whether the BXD family is suitable as a diversity model to define causal molecular networks modulating SARS pathogenesis and disease severity, we investigated whether the two founders, B6 and D2, differ significantly in susceptibility to MA15 infection. We first examined our existing transcriptomic data on the B6 and D2 parents and found that basal pulmonary levels of viral entry receptor Ace2 transcript are well matched [ 8 ], ruling out the possibility of pre-infection Ace2 expression as a confounding factor. We then challenged groups of 10-week old B6 ( n = 26) and D2 ( n = 28) via the intranasal route with 10 5 TCID 50 of MA15 virus (diluted in 50-μl phosphate-buffered saline, PBS), and monitored weight changes for 9 days.…”
mentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2) is the major receptor for SARS-CoV-2 7, 8 . This receptor’s inducibility and variability are proposed to be an essential element for viral tropism, infectivity, and COVID-19 disease progression and outcomes [9] , [10] , [11] , [12] , [13] , [14] . ACE2, a vital member of the renin-angiotensin system (RAS), is a monocarboxyl peptidase and type I transmembrane protein 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These agents damage the ciliated cell, often resulting in cell death and ciliated cell hypoplasia. Notch pathway components were identified as susceptibility genes for lung damage ( 16 ), viral entry ( 17 ), and hyperinflammation ( 18 ). Consequently, treatments that specifically target Notch pathway components have the potential to normalize ciliated and goblet cell frequency, restore mucociliary clearance, and improve the health of people with chronic lung disease.…”
Section: Introductionmentioning
confidence: 99%